Teologi Kerukunan Umat Beragama: Studi pada Masyarakat Desa Boneana, Kupang Barat - Marla Marisa Djami (Sekolah Tinggi Teologi Torsina Surakarta, 2021)
This study intends to describe the religious harmony in Boneana village. Communi-cation between religious communities is still tenuous. The harmony between religious communities in Bonenana can be used as an example in national life. The system for regulating religious communities is not yet optimal. This research approach is qualitative, data obtained through interviews with the Boneana community. The results of the analysis show that religious differences are not a barrier to mutual help. The trauma caused by the conflict after evacuating from Timor Leste made the people of Boneana want to live in peace. Harmony in the Boneana community is built on mutual respect for one another. The dialogue carried out by the Bonenana community is informal, where dialogue is in everyday life. The difference is a platform used by the people in Bonenana to build a sense of belonging. The people in Boneana have carried out harmony according to the principle of harmony theology.AbstrakPenelitian ini bermaksud memaparkan kerukunan beragama di desa Boneana. Komunikasi antar umat beragama masih renggang. Kerukunan antar umat beragama di Bonenana dapat dijadikan contoh dalam kehidupan berbangsa. Sistem pengaturan umat beragama belum masksimal. Pendekatan penelitan ini adalah kualitatif. Data didapatkan melalui wawancara terhadap masyarakat Boneana. Hasil analisis memperli-hatkan bahwa perbedaan agama tidak menjadi penghalang untuk saling membantu. Trauma akibat konflik pasca mengungsi dari Timor Leste membuat masyarakat Boneana ingin hidup damai. Kerukunan di masyarakat Boneana dibangun dalam sikap saling menghargai satu sama lain. Dialog yang dilakukan masyarakat Bonenana bersifat informal, di mana dialog dalam kehidupan sehari-hari. Perbedaan merupakan wadah yang dipakai masyarakat di Bonenana untuk membangun rasa saling memiliki. Masyarakat di Boneana telah menjalankan kerukunan sesuai pokok teologi kerukunan.